Accidental Aluminum Phosphide Intoxication Successfully Treated with Hyperbaric Oxygen Therapy: A Case Report - Hájek, Michal; Chmelař, Dittmar; Tlapák, Jakub; Rybárová, Veronika; Ondra, Peter; Halouzka, Vladimír (Toxics, 2024)
The most common pesticide agents are organophosphates and phosphides, aluminum phosphide (ALP) in particular. ALP is a major cause of suicidal poisoning in many countries. In other countries, the problem of accidental, mainly occupational-related, poisoning is also real and actual. Almost two thirds of individuals in poisoning cases have died. This case report describes a case of a patient with accidental ALP intoxication. The origin of the poisoning was the fumigation of stored grain in an agricultural building adjacent to the building in which patient was temporarily housed, while both buildings were connected by an underground corridor, through which the released poison gas penetrated. The case was originally presented by the rescuers as well as healthcare professionals of the local hospital as carbon monoxide intoxication, which has a similar symptomatology as ALP intoxication. The patient was treated comprehensively, including using the HBOT method, which is very unique in the case of phosphine intoxication in human medicine, with an excellent final clinical outcome. This was the first described case of HBOT for ALP intoxication in clinical medicine, although the HBOT indication itself became a coincidence in this case. Further studies must be undertaken to demonstrate the effectiveness of HBOT in treating patients with ALP poisoning.